Efficacy of cryodehydration technique in preserving the gross and histoarchitectural details of goat visceral and musculoskeletal specimens (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study sought to determine the effectiveness of the cryodehydration technique in preserving the morphologic and morphometric attributes of the anatomical specimens of goats. Materials and methods: Different anatomical parts of a goat, i.e., heart, lungs, spleen, liver, kidney, and musculoskeletal specimens, were collected and fixed in 15% formalin. Later on, the fixed specimens were cryodehydrated by fast freezing (burning process) and repeated freezing-thawing sessions, followed by wood glue coating. Finally, the macroscopic (i.e., weight, color, texture, odor, and durability) and microscopic characteristics (by routine hematoxylin and eosin staining) of the cryodehydrated specimens were studied. Results: The resultant specimens produced excellent color and texture and were lightweight (60%–80% weight loss), soft, dry, odorless, durable, and easy to handle. The histoarchitectural details of the heart and skeletal muscle were well preserved, while some distinctive alterations were observed in the parenchymatous organs, i.e., breach in cellular integrity, loss of cell cytoplasm, loss of cytoplasmic and nuclear clarity, increased sinusoidal space, dilatation of the renal tubules, and reduction in glomerular size. Nevertheless, the basic histoarchitecture of each specimen was yet to be distinctly identifiable. Conclusion: The current study findings suggest that the cryodehydration technique can preserve gross anatomical features as well as histoarchitectural details and can be an effective tool for facilitating veterinary education and research.J. Adv. Vet. Anim. Res., 10(4): 720–729, December 2023http://doi.org/10.5455/javar.2023.j727